Hierarchical Model of Assessing and Selecting Experts; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Chernysheva T. Yu. Tatiana Yurievna; Korchuganova M. A. Marina Anatolievna; Borisov V. V.; Minkov S. L. (2016, 2016)
Title screen